Morphological and Genetic Diversity Study of Upland Rice Varieties under Rain-fed Environment - Zeleke, Bantalem; Worede, Fisseha (Journal of Tropical Crop Science, 2022)
A field experiment was conducted at Fogera Northwest Amhara region to study the morphological traits to variability in 20 upland rice varieties, consisting of nine NERICA and eleven parents. The data were collected from ten randomly selected plants of each plot (plant height, panicle length, culm length, flag-leaf length, number of spikelet per panicle, number of grains per panicle, number of filled grains per panicle, numbers of fertile tillers per plant, yield per plant) and from plot bases (days to heading, days to maturity, grain-filling period, thousand-seed weight, biomass yield, grain yield, and harvest index). The results of the principal component analysis showed that four components account for 76.7% of the total variation, giving a clear idea of the structure underlying the variables analysed. Cluster analysis using un-weighted Pair Group Method using Arithmetic Average linkage (UWPGMA) classified the twenty varieties into five distinct groups. The maximum inter-cluster distances were; recorded 8.05 between cluster I & V, 6.67 between cluster I and IV; and 5.5 between Cluster I and III, indicating that the possibility of high heterosis if individuals from these clusters are cross bred. The results of the principal component analysis were closely in line with those of the cluster analysis. This study has provided useful information, on evaluation of genetic diversity of rice varieties and will indicate the way, how plant breeders screen out large populations and to develop new breeding protocols for rice improvement.